Bank Reform and Bank Efficiency in Pakistan. (IMF Working Papers; Working Paper ;, 2001)
Pakistan undertook major financial sector reforms starting in the late 1980s. The effects of these reforms on the profitability and cost and revenue efficiency of the banking sector are evaluated. The revenue performance of all banks, and especially the privatized banks, improved significantly, although costs also rose and relative performance across banks did not converge.